Understanding How Physical Exercise Improves Alzheimer’s Disease: Cholinergic and Monoaminergic Systems - Zong, Boyi; Yu, Fengzhi; Zhang, Xiaoyou; Zhao, Wenrui; Sun, Peng; Li, Shichang; Li, Lin (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is an age-related neurodegenerative disorder, characterized by the accumulation of proteinaceous aggregates and neurofibrillary lesions composed of β-amyloid (Aβ) peptide and hyperphosphorylated microtubule-associated protein tau, respectively. It has long been known that dysregulation of cholinergic and monoaminergic (i.e., dopaminergic, serotoninergic, and noradrenergic) systems is involved in the pathogenesis of AD. Abnormalities in neuronal activity, neurotransmitter signaling input, and receptor function exaggerate Aβ deposition and tau hyperphosphorylation. Maintenance of normal neurotransmission is essential to halt AD progression. Most neurotransmitters and neurotransmitter-related drugs modulate the pathology of AD and improve cognitive function through G protein-coupled receptors (GPCRs). Exercise therapies provide an important alternative or adjunctive intervention for AD. Cumulative evidence indicates that exercise can prevent multiple pathological features found in AD and improve cognitive function through delaying the degeneration of cholinergic and monoaminergic neurons; increasing levels of acetylcholine, norepinephrine, serotonin, and dopamine; and modulating the activity of certain neurotransmitter-related GPCRs. Emerging insights into the mechanistic links among exercise, the neurotransmitter system, and AD highlight the potential of this intervention as a therapeutic approach for AD.